AS INJUNÇÕES AOS DOCENTES NA UNIVERSIDADE PÚBLICA: DE INTELECTUAIS A TRABALHADORES POLIVALENTES - Costa, Áurea De Carvalho [UNESP] (Fundação Oswaldo Cruz, Escola Politécnica de Saúde Joaquim Venâncio, 2016)
We present part of the research on the precariousness of teaching in Brazil. It is an in-depth discussion about teaching in higher education, in the present context. The hypothesis is that these teachers are submitted to the alienation and precariousness of labor by means of the recruiting, selection, hiring and evaluation policies, that deprives them of control over their work. Taking historical and dialectical materialism as reference, we utilized documental analysis to study the case of a state university. We identified as indications of the precariousness of teaching: the application of institutional evaluations for the management of the teaching staff; staff cuts; the substitution of disciplines for internships and teaching practice; e-learning; the lack of retirement recognition policies; and the policies that impose a productivist logic to the teachers in activity.

Presentamos parte de la investigación sobre la precarización del trabajo docente en Brasil. Trata-se de un texto de profundización de la discusión sobre docencia en el enseño superior en el contexto actual. La hipótesis es la de que esos docentes son sometidos a la alienación y a la precarización del trabajo, por medio de políticas de reclutamiento, selección, contratación y evaluación que os destituyen del controle sobre el trabajo. Con base en el referencial del materialismo histórico y dialectico, utilizamos el análisis documental para estudiar el caso de una universidad estadual. Identificamos como indicios de la precarización del trabajo docente: las aplicaciones de evaluación institucional para gestión del personal docente; la redacción de los cuadros; la sustitución de disciplinas por prácticas profesionales en licenciaturas; el enseño a la distancia; la carencia de políticas de valorización del aposentado; y las políticas que ponen a los activos a lógica productivista.

Apresentamos parte da pesquisa sobre a precarização do trabalho docente no Brasil. Trata-se de um texto de aprofundamento da discussão sobre docência no ensino superior no contexto atual. A hipótese é a de que esses docentes são submetidos à alienação e à precarização do trabalho, por meio de políticas de recrutamento, seleção, contratação e avaliação que os destituem do controle sobre o trabalho. Com base no referencial do materialismo histórico e dialético, utilizamos a análise documental para estudar o caso de uma universidade estadual. Identificamos como indícios da precarização do trabalho docente: as aplicações de avaliação institucional para gestão do pessoal docente; a redução dos quadros; a substituição de disciplinas por estágios e práticas em licenciaturas; o ensino à distância; a carência de políticas de valorização do aposentado; e as políticas que impõem aos ativos a lógica produtivista.
THE INJUNCTIONS TO PUBLIC UNIVERSITY TEACHERS: FROM INTELLECTUALS TO POLYVALENT WORKERS
LOS MANDATOS A LOS DOCENTES EN LA UNIVERSIDAD PÚBLICA: DE INTELECTUALES A TRABAJADORES POLIVALENTES
Keywords: higher education; intellectuals; university; teaching work; educational policies; ensino superior; intelectuais; universidade; trabalho docente; política educacional